Associations between socioeconomic status and adherence to hypertension treatment among older adults in urban and rural areas in Myanmar: a cross-sectional study using baseline data from the JAGES in Myanmar prospective cohort study. Issue 1 (17th January 2023) - Nagamine, Yuiko; Shobugawa, Yugo; Sasaki, Yuri; Takagi, Daisuke; Fujiwara, Takeo; Khin, Yu Par; Nozaki, Ikuma; Shirakura, Yuki; Kay Thi, Lwin; Poe Ei, Zin; Thae, Zarchibo; Win, Hla Hla
Abstract : Objectives: This study aims to investigate whether there is a differential association between socioeconomic status (SES) and adherence to hypertension medication among older adults in rural and urban areas in Myanmar and assess what type of SES is associated with a difference. Design: Cross-sectional study using baseline data from the Japan Gerontological Evaluation Study in Myanmar prospective cohort study. A multistage random sampling method was applied in each region. Setting: An urban and a rural area in Myanmar. Participants: A total of 1200 older adults over 60 years old in Myanmar were randomly selected in 2018 (600 each from rural and urban areas). Of them, 573 had hypertension and were eligible for the analysis (urban: 317, rural: 256). Outcome: Adherence to hypertension medication (yes/no) is the outcome of interest. Three types of SES (wealth, education and current employment status) were the independent variables. Results: We found that 21.5% of urban residents and 48.4% of rural residents were non-adherent in the study population. Poisson regression modelling stratified by area was performed to estimate the prevalence ratios (PRs) of not following treatment instructions. Demographic information and complications of hypertension were adjusted for in all models as possible confounders. In terms of SES, middle level of wealth compared with low level was significantly associated with poor adherence (PR 2.68, 95% CI 1.28 to 5.59) in the urban area, but education and employment status did not show similar associations. Lower education compared with middle/high school or higher was significantly associated with poor adherence in the rural area (no school: PR 3.22, 1.37–7.58; monastic: 3.42, 1.16–5.07; primary school: 2.41, 1.18–4.95), but wealth and income did not show similar associations. Conclusions: SES and adherence to hypertension medication were differently associated among older adults in rural and urban areas in Myanmar. To ensure healthcare access to hypertension treatment for every citizen, the differential association between SES and adherence in urban/rural areas needs to be recognised.